Pre-Feasibility Study of Carbon Sequestration Potential of Land Clearing Stumps Buried Underground - Laitila, Juha; Sikanen, Lauri; Väätäinen, Kari (Faculty of Forestry, University of Zagreb, 2023)
Stump harvesting for energy has decreased in Finland, and many heat and power plants no longer accept stumps in their fuel portfolio due to fuel quality problems. However Finland is a forested country, and land clearing stumps need to be extracted, e.g. in infrastructure construction projects. If stumps cannot be used for energy production, they are dumped in landfills, where they start to decay and release CO2 into the atmosphere. One option to avoid CO2 emissions would be the burying of stumps underground so that the decaying process of wood would be inhibited in anaerobic conditions. The aim of this study was to define the carbon sequestration potential of stump burying logistics and calculate their CO2-eq emissions to compare them with the emissions of decaying stumps in piles. The analysis was performed as a spreadsheet-based system analysis at a worksite level as a function of time and size of extracted stumps. As a result of the analysis, the emission effiency of the logistics chain based on stumps stored below the ground was good. The net carbon stock varied between 743.7 and 775.0 kg CO2-eq/m3 as a function of stump diameter, when the emissions of the stump burying logistics chain were 49.0 and 17.7 kg CO2-eq/m3 respectively. In the case of a Finnish municipality with an annual accumulation of 1000 m3 of land clearing stumps, the carbon sequestration potential of stumps buried underground is equivalent to the emissions of between 280,000 and 290,000 liters of diesel fuel consumption, depending on the diameter of the extracted stumps and the diesel fuel emission factors for different engine and diesel fuel types.
Keywords: carbon storage; climate change; mitigation; CO2 emissions; logistics; stump and root biomass; fuel consumption